Gateway User Interface Design for Distributed Wireless Monitoring Platform using Raspberry Pi (DWMP) - Muhammad Mirza Amsyar bin Noor Azeb; Saparudin, Faiz Asraf; Mohd Redzuan, Ahmad Afif Aiman; Mohd Shah, Nor Shahida; Shamsuddin, Muhammad Khairi Azizi (Progress in Engineering Application and Technology, 2021)
Distributed Wireless Monitoring Platform (DWMP) is the system that available to collect data of water quality in several of places within range of large distance for research purposes with the aim of improving collect and monitor operations. There are two important aspects for the operations which is data collection and management. Without data management system, it is hard for user to interpret their data efficiently and presenting the data clearly. One of the main components of the system is to design a fully functional web-based server using Linux, Apache, MySQL, PHP (LAMP) architecture in Raspberry Pi platform that can display accurate data obtained from sensor in real time. This project focuses on providing attractive and responsive user interface to the end user to help in collect and monitor process which can be accessed through smartphone, tablets, or personal computer. The data are stores in concept of centralized storage that one of the simplest data storage strategies. There are three crucial data collected and displayed in this web server. Timestamp, water quality index, are obtained from sensor nodes while the signal strength is obtained from the LoRa. Besides that, the user interface also being evaluate using system usability scale (SUS) which is to improve the design and functionality. The user interface design is based on HTML which is lightweight while providing crucial information to the researchers or authorities such as water quality index versus timestamp graph, signal strength indicator, and data table which consist of timestamp, water quality index and signal strength of the sensor nodes in real time. Based on system usability scale (SUS), the user interface of the system has been evaluated which improve the capability of the website and also user-friendly. The users are confidently to use and understand the functionality of the website without having a technical person. Overall, the design implementations able to generate a feasible system that can be used in collect and monitor operation in the future in order to save keep the health of river.